Review paperGenital ulcer diseases as an entry for HIV infection - Duś, Monika; Łuczkowska, Magdalena; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Genital ulcer diseases (GUDs) are documented agents facilitating HIV-1 infection. The main pathogens causing GUDs are: Herpes simplex virus (HSV), Treponema pallidum and Haemophilus ducreyi. It is suggested that these diseases may increase the risk of HIV transmission even a hundredfold. A few mechanisms facilitating HIV penetration into the organism are considered. The first one is disruption of the epidermis or mucous membranes, creating a physical entry point for an infection. The next one is an increased number of inflammatory infiltration cells such as macrophages and T-lymphocytes. Increased expression (up-regulation) of HIV co-receptors – CCR5 and CXCR4 – on the surface of macrophages and lymphocytes in lesions is an additional risk factor of HIV infection. In the paper relationships between GUDs and HIV acquisition are described.